Smart Security Guard Scheduling System Based on the Reinforcement Learning - Cheng Jiang (2019)
© 2017 IEEE. The securities of some specific areas are important. This paper depicts an intelligent security guard scheduling system. The main purpose of this paper is to demonstrate a security guard system associated with study module performing better than the one with fixed patrol path. The main components of this system are two levels heat map with evaporation mechanism and a saltatory path constructor. They work together to assist system scheduler in defining the patrol paths. The performance of the solution is calculated by our designed formula. In the content, the problem definition, the framework, and the comparison result are discussed in this paper.